Production and characterization of amylase obtained from Rhizopus microsporus var. oligosporus (Research, Society and Development, 2020)
Amylases have the ability to catalyze the α-1,4 binding of starch by releasing glucose and dextrin, with prominence in several industrial fields. The research sought to characterize the enzyme amylase obtained from the fungus Rhizopus microsporus var. oligosporus, through the Doehlert methodology, evaluating the behavior of the enzyme in the face of variations in pH and temperature. The production of amylase occurred with the use of starch as an inducer, and the characterization was carried out using the response surface methodology, with pH analysis at 5 levels (3.0, 4.0, 5.0, 6.0 and 7.0) and temperature in 3 levels (30, 50 and 70°C). The evaluation of the amylase thermostability occurred at 60, 70 and 80ºC. The application of the experimental model indicated that the amylase obtained from R. microsporus var. oligosporus shows better catalytic development at temperatures between 40ºC and 55ºC and pH between 2.5 and 3.2. The evaluation of thermostability indicated that the increase in temperature negatively influences the catalytic activity of amylase. The experimental model led to the understanding of the conditions favorable to the production of amylases from R. microsporus var. oligosporus.